Critical Effects of Smoking Parameters on the Levels of Polycyclic Aromatic Hydrocarbons in Traditionally Smoked Fish and Meat Products in Finland - Mirja Hokkanen; Ulla Luhtasela; Pirkko Kostamo; Tiina Ritvanen; Kimmo Peltonen; Marika Jestoi (Journal of Chemistry)
Eighty fish products and 62 meat products were sampled and analysed in Finland, in the year of 2012 for four marker polycyclic aromatic hydrocarbons (PAH4) with an accredited gas chromatography-tandem mass spectrometry method. In general, the determined PAH4 levels were relatively low and below the maximum levels. The mean concentrations of smoked fish samples were 0.7 μg·kg−1 for benzo[a]pyrene and 3.9 μg·kg−1 for the PAH4 sum, whereas in smoked meat samples, mean benzo[a]pyrene and PAH4 sum levels were 2.2 μg·kg−1 and 11 μg·kg−1, respectively. However, PAH4 sum concentrations ranged from not detected to 200 µg·kg−1 particularly among meat products, underlining the importance of controlling the smoking process. In this study, the effect of selected smoking parameters, i.e., smoking technique (direct/indirect), smoking time (less than five hours/more than five hours), smoke generation temperature (optimised/nonoptimised), and the distance (less than five metres/more than five metres) between the food and the smoke source, confirmed the linkage between the smoking factors and the PAH4 levels formed in fish and meat products. As guidance for a safe smoking process, it was demonstrated that an indirect smoking technique, a shorter smoking time, an optimised smoke generation temperature, and a longer distance from the smoke source generated lower PAH concentrations in food products. However, while a shorter smoking time generated lower PAH levels in meat products, the levels in fish products were unexpectedly higher than in those smoked for a longer time. Other factors, such as the smoking type (cold smoking/warm or hot smoking) and the fish size, may have affected this result.